The influence of diabetes psychosocial attributes and self-management practices on change in diabetes status - Zulman, Donna M. (2011)
OBJECTIVE: To examine the influence of diabetes psychosocial attributes and self-management on glycemic control and diabetes status change. METHODS: Using data from the Health and Retirement Study, a nationally-representative longitudinal study of U.S. adults > 51 years, we examined cross-sectional relationships among diabetes psychosocial attributes (self-efficacy, risk awareness, care understanding, prioritization of diabetes, and emotional distress), self-management ratings, and glycemic control. We then explored whether self-management ratings and psychosocial attributes in 2003 predicted change in diabetes status in 2004. RESULTS: In multivariate analyses (N = 1834), all diabetes psychosocial attributes were associated with self-management ratings, with self-efficacy and diabetes distress having the strongest relationships (adj coeff = 8.1, p < 0.01 and −4.1, p < 0.01, respectively). Lower self-management ratings in 2003 were associated cross-sectionally with higher hemoglobin A1C (adj coeff = 0.16, p < 0.01), and with perceived worsening diabetes status in 2004 (adj OR = 1.36, p < 0.05), with much of this latter relationship explained by diabetes distress. CONCLUSION: Psychosocial attributes, most notably diabetes-related emotional distress, contribute to difficulty with diabetes self-management, poor glycemic control, and worsening diabetes status over time. PRACTICE IMPLICATIONS: Self-management and adherence interventions should target psychosocial attributes such as disease-related emotional distress.